1997
DOI: 10.1038/sj.onc.1200923
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridisation of ductal carcinoma in situ of the breast: identification of regions of DNA amplification and deletion in common with invasive breast carcinoma

Abstract: Comparative genomic hybridisation has been used to map copy number changes in nine cases of ductal carcinoma in situ of the breast obtained from waxembedded archive material. A wide variety of abnormalities were detected including gain of regions of 1q, 17q, 19q, 20p and 20q and loss on 13q, 14q, 17p, 16q and 22q. Ampli®cation of areas on 10p, 8q and 20q were also observed. Chromosomal alterations were more frequent in higher grade DCIS and closely resemble those previously detected in invasive breast cancer u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 17 publications
10
53
0
Order By: Relevance
“…Our results are consistent with previous studies, revealing increased copy numbers on chromosomal arm 10p in breast cancer (Ried et al, 1995;James et al, 1997;Murphy et al, 1995).…”
Section: Tpl-2 Gene Ampli®cation In Human Breast Tumourssupporting
confidence: 94%
“…Our results are consistent with previous studies, revealing increased copy numbers on chromosomal arm 10p in breast cancer (Ried et al, 1995;James et al, 1997;Murphy et al, 1995).…”
Section: Tpl-2 Gene Ampli®cation In Human Breast Tumourssupporting
confidence: 94%
“…One purpose of the study had been to attempt to gain more information about the natural history of breast cancer and the molecular changes accompanying progression. This study and (James et al, 1997) have confirmed that genetic changes found in DCIS lesions are similar to those found in invasive breast carcinoma. Furthermore, a recent paper has also described some changes in morphologically normal tissue adjacent to breast carcinomas (Deng et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…In prostate carcinoma, loss of 8p12 ± 21 is an early event occurring in 63% of intraepithelial neoplasia . Similarly, the involvement of 8p22 ± p23 region is considered as an early event as suggested by allelic losses detected in in situ bladder carcinoma, in situ ductal carcinoma of the breast or preinvasive head and neck squamous cell carcinoma (Rosin et al, 1995;El-Naggar et al, 1995;James et al, 1997). In HCC, loss of 8p appear as a crucial event in tumorigenesis as it is sometimes the only allelic imbalance detected in tumors (Boige et al, 1997).…”
Section: Discussionmentioning
confidence: 99%